Creating Awareness for Primary Immunodeficiencies in Japan - Takada, Hidetoshi (Frontiers in Immunology, 2021)
Primary immunodeficiency (PID) is primarily characterized by susceptibility to infectious diseases. In addition, patients with some type of PID are prone to develop autoimmune, autoinflammatory, or malignant diseases. Therefore, the term, inborn errors of immunity (IEI), has been more used rather than PID. In recent years, the number of diseases which belong to PID has been increasing. There were approximately 110 diseases in the report of International Union of Immunological Societies in 1999. Since then, the number increased to 430 diseases in the latest IUIS report in 2019. We conducted PID nationwide survey in Japan for 3 times in the last 15 years. These studies were focused on incidence and complications of PID, the clinical course of viral infection, and methods to prevent infectious diseases in PID patients. For the awareness of PID, it is essential to know the general and fundamental information of PID patients. Needless to say, we need it to offer appropriate medical services for PID patients. Moreover, chances to provide answers to the questionnaires and seeing the results of the analysis should contribute to the awareness of PID among doctors. In this review, I am going to summarize the results of 3 nationwide survey in Japan, and pick up interleukin-1 receptor-associated kinase 4 (IRAK4) deficiency as an example for creating awareness for its appropriate management.